2023
DOI: 10.1186/s40359-022-01035-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of resilience among university students in Oman: a cross-sectional study

Abstract: Background Resilience has a paramount role in dealing with different life stressors and has a great impact on mental health. Aim To assess the level of resilience among university students and explore the relation between resilience and a number of variables including psychological well-being, self-esteem and physical health. Methods A cross-sectional design was utilized. Data was collected from 676 un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
(55 reference statements)
5
6
1
Order By: Relevance
“…Our results showed that gender exhibited a statistically significant relationship with low resilience, whereas females were more liable to low resilience. This contradicts a previous study in Oman, which showed no significant difference in the level of resilience across genders [ 49 ]. However, it has been shown that males are more resilient than females in general [ 54 56 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results showed that gender exhibited a statistically significant relationship with low resilience, whereas females were more liable to low resilience. This contradicts a previous study in Oman, which showed no significant difference in the level of resilience across genders [ 49 ]. However, it has been shown that males are more resilient than females in general [ 54 56 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Our study showed low and high resilience prevalences of about 49.9% and 3.2%, respectively. In accordance with our results, a study conducted in Oman revealed similar prevalences of low and high resilience of 45.3% and 5.5%, respectively [ 49 ]. Basically, resilience research has primarily focused on Western-based outcomes, and there is a lack of cross-cultural validation of findings and rigorous investigations associated with resilience in non-western cultures [ 50 ].…”
Section: Discussionsupporting
confidence: 92%
“…A previous study found a moderate level of resilience among university students in Jordan, with resilience being negatively correlated with depression (Hamdan-Mansour et al, 2014). Another study also found moderate levels but with different correlates of resilience and meaning in life (Al Omari et al, 2023) 123,3/4 relationship between academic achievement and resilience, and they found that students with a higher level of resilience had better academic achievement (Labrague et al, 2018;Laher et al, 2021). This literature review follows this framework's pathways, as shown in Figure 1, linking meaning in life, resilience and psychological stress among university students.…”
Section: Introductionmentioning
confidence: 93%
“…With many online teaching and learning improvements, university students have started adapting to this new normal. Previous studies reported that a resilient individual has a dynamic adaptive process to manage stress (Al Omari et al ., 2023). Resilience is also linked with life satisfaction (Cosco et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation